(untitled) (Sahel Journal of Life Sciences FUDMA, 2025)
A diagnostic technique that is easy to perform, sensitive, and specific is critically essential in any disease control plan. This study aimed to determine the viability of using saliva in the diagnosis of Plasmodium falciparum, using rapid diagnostic test (RDT) kits in Dutsin-ma, Katsina, Nigeria. Blood and saliva samples from suspected malaria patients were obtained and analysed for the detection of Plasmodium falciparum histidine-rich protein 2 using pfhrp2 antigen detection kits (First Response and Arkray). Malaria parasitaemia count was also determined by microscopy. The sensitivities and specificities of both RDT-blood and RDT-saliva were compared. The results from 376 suspected malaria patients who provided both blood and saliva samples for this study revealed a prevalence rate of 54.3% for Plasmodium falciparum infection by RDT-blood. The sensitivities of RDT-blood and RDT-saliva were 53.57% and 10.36%, respectively. It was also observed that RDT-saliva missed many positive cases, especially in patients with low parasitaemia counts confirmed by microscopy.